PENGARUH PERPUTARAN KAS DAN PERPUTARAN PERSEDIAAN TERHADAP LABA BERSIH PADA PT AKASHA WIRA INTERNATIONAL Tbk PERIODE 2008-2015 - Teguh Supriyadi; Evi Adriani; Yunan Surono (Universitas Batanghari Jambi, 2017)
Inventory turnover is the ratio used to measure funds invested in this inventory rotating in one period can be interpreted also that inventory turnover is a ratio that shows how many times the amount of inventory items replaced in one year. The greater this ratio will be better for the company and vice versa. From result of hypothesis testing can be concluded that variable of cash turnover (X1) and inventory turnover (X2) to variable (Y) or net profit is 47,7% and 52,3% influenced by other variation not examined in this research. Based on the coefficient values contained in the table of multiple linear regression equations prepared for this study is Y = 4.166 + 0.861 X1 - 0.410 X2. From the multiple linear regression equation above it can be in the constant analysis of 4.166 shows if the variable cash turnover and inventory turnover constant or equal to zero, net income of 4.166 Rupiah, changes in variable cash turnover has a value of regression coefficient of 0.861 Coefficient marked positive means that each An increase in cash turnover of 1 time will result in a decrease in net income of 0.861 Rupiah, changes in inventory turnover variables have a regression coefficient value of -0.410 Coefficients are negative, meaning that any increase of 1 time will result in a net profit increase of -0.410 Rupiah. The results of this study indicate that Cash Turnover and Inventory Turnover (simultaneously) have a significant effect on net income. This is indicated by using F test, where F arithmetic is 13.237 > F table α = 0.05 of 3.34 or F arithmetic > F table (13.237 < 3.34). Cash turnover variables and inventory turnover can account for net income change of 47,7% while 52,3% is explained by other variables.Keyword: cash turnover, net profit